2002
DOI: 10.1590/s0102-37722002000300013
|View full text |Cite
|
Sign up to set email alerts
|

Envolvimento dos receptores 5-HT2 da amígdala nos níveis de ansiedade induzidos pela exposição de ratos ao labirinto em cruz elevado

Abstract: O efeito de microinjeções intra-amigdalóides do antagonista 5-HT2A/2C de receptores serotoninérgicos RP 62203 (1,0; 2,5; 5,0 mg) foi investigado em medidas tradicionais e etológicas (esquadrinhar, espreitar e explorações da extremidade) de ansiedade de ratos no labirinto em cruz elevado. A dose de 5,0 mg aumentou as porcentagens de entrada e de tempo nos braços abertos, sem alterar no número de entradas nos braços fechados. As categorias esquadrinhar, espreitar e explorações da extremidade também foram alterad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(35 reference statements)
1
1
0
Order By: Relevance
“…The anxiolytic effect induced by ketanserin during training could be explained by the antagonism of the 5-HT 2A-C receptors. This finding corroborated the study of Pinheiro et al (2002), who injected a different 5-HT 2A antagonist (RP62203) in the basolateral amygdala and found an increase in exploration of the open arms. In addition, increased exploration of the final third of the open arm was also observed in the ketanserin group (Supplemental Table 2), which has also been seen in another study after intraperitoneal injection of 5-HT 2A antagonists (Setem et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The anxiolytic effect induced by ketanserin during training could be explained by the antagonism of the 5-HT 2A-C receptors. This finding corroborated the study of Pinheiro et al (2002), who injected a different 5-HT 2A antagonist (RP62203) in the basolateral amygdala and found an increase in exploration of the open arms. In addition, increased exploration of the final third of the open arm was also observed in the ketanserin group (Supplemental Table 2), which has also been seen in another study after intraperitoneal injection of 5-HT 2A antagonists (Setem et al, 1999).…”
Section: Discussionsupporting
confidence: 89%
“…For example, Christianson et al (2010) showed the involvement of 5-HT 2C receptors in the expression of anxiety using a model of posttraumatic stress disorder. Conversely, the injection of RP62203 (a 5-HT 2A–C receptor antagonist) into the BLA induced anxiolytic effects in the plus-maze task (Pinheiro et al, 2002), whereas 8-OH-DPAT [(±)-8-hydroxy-2-(di-n-propylamino) tetraline] (a 5HT 1A receptor agonist) into the BLA produced anxiogenic effects in the social interaction test in rats (Gonzalez et al, 1996). Blockade of 5-HT receptors with methysergide in the BLA rescued immobility behavior in the forced swim test induced by odor cue paired to infant trauma (electrical shock) in rats (Rincón-Cortés et al, 2015).…”
mentioning
confidence: 99%